PERLINDUNGAN HUKUM TERHADAP PENGGUNA SOSIAL MEDIA TERKAIT CYBER CRIME PHISING BERDASARKAN UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Reyhan, Edlin; Gultom, Potler (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
Crime phishing is a crime Cyber Crime what happens in the digital world. Protection of social media users against phishing crimes is regulated in the ITE Law and the personal data protection law. Therefore, the aim of this research is to find forms of accountability for phishing crimes and legal protection for phishing crimes. This research uses a normative juridical approach. The author conducted research using secondary data literature studies in the form of primary, secondary and tertiary legal materials, and field studies that correlate with the object of this research. This research concludes that protection against phishing crimes is contained in Article 4, Article 15 paragraph (1), and Article 66 and Article 67 of the Personal Data Protection Law, while responsibility for phishing crimes is contained in Article 35 of the ITE Law in conjunction with Article 51.